Transcriptome and 16S rRNA analysis revealed the response of largemouth bass (Micropterus salmoides) to Rhabdovirus infection - Fei, Hui; Yi, Shun fa; Zhang, Hui min; Cheng, Yan; Zhang, Ya qi; Yu, Xiang; Qian, Shi chao; Huang, Meng meng; Yang, Shun (Frontiers in Immunology, 2022)
To better understand the response of largemouth bass (Micropterus salmoides) to Micropterus salmoides rhabdovirus (MSRV) infection, we investigated the intestinal bacterial structure and transcriptome profile of fish at 72 hours post-infection(hpi). Total of 1574 differentially expressed genes (DEGs) were identified in largemouth bass spleen following MSRV infection, including 573 upregulated and 1001 downregulated genes. KEGG and GO enrichment analysis revealed that upregulated genes were enriched in antiviral related signaling pathway, including NLR signaling pathway, RLR signaling pathway and regulation of the IFN-γ-mediated signaling pathway, whereas some immune-related DEGs enriched in FA and ECM-receptor interaction(ECM-RI) were downregulated, as well as genes associated with metabolic processes, such as PPAR, adipocytokine signaling pathway, Glycerolipid and Retinol metabolism. Furthermore, the principal component analysis (PCA) and phylogenetic analysis revealed that MSRV infection significantly affected the microbiota of largemouth bass intestine; the LEfSe analysis showed that relative abundances of Acidobacteria, Actinobacteria, Chloroflexi, Alphaproteobacteria, Betaproteobacteriales, and Streptococcus in the fish intestinal were significantly increased following MSRV infection. Additionally, a high correlation was determined between the expressions of interferon-related upregulated genes and the relative abundance of Streptococcus, Escherichia-Shigella by redundancy analysis (RDA). These results collectively illustrated that intestinal microbiota composition might be associated with the immune-related gene expression in largemouth bass in response to MSRV infection.